The Concept Of Criminalization Of Prostitution As A Legal Instrument For The Renewal Of Indonesian Criminal Law - I Dewa Agung Gede Mahardika Martha; I Ketut Rai Setiabudhi; Erny Herlin Setyorini (Jurnal Hukum Prasada, 2023)
Prostitution is the activity of sexual intercourse for livelihood, there are several goals to be obtained, such as money, goods or gifts and also the satisfaction of inner desires so that it includes not only copulation but some to be achieved or owned. Prostitution activities are included in the form of sexual deviance, which deviate from the social, religious, polite and moral values of the Indonesian nation. In other words, it also injures or abuses the values contained in Pancasila. Therefore, the urgency of criminialization in prostitution in the current Indonesian criminal law and the concept of criminalization of prostitution in the context of renewing Indonesian criminal law. This research uses a normative type of legal research. The urgency of criminialization in prostitution in Indonesian criminal law can be seen in four foundations, namely philosophical, juridical, sociological, and human rights foundations. Regulations on the practice of prostitution as a criminal act or against materril law currently in Indonesian criminal law still do not reflect the principle of justice and the principle of expediency.